Changes in pH of legume cell suspension culture media containing aluminum. - Mahmood, Marziah (1990)
When different levels of aluminum was added to the L-6 liquid media there was a marked decrease in pH values. The wide pH shift obtained indicated that pH adjustments prior to the addition of aluminum were essential in order to standardise the initial pH of all treatments at 4.0 ± 0.1. The pH adjustments made to the L-6 liquid media prior to autoclaving for treatments 0, 50, 100, 200, 400, 600, and 800 uM Al were 4.4, 5.1, 5.6, 5.9, 6.1, 6.6, and 7.6, respectively. When the respective levels of Al were added the pH of the media of each treatment was found to be about 4.0 ± 0.1. Further examinations showed that the pH of the culture media containing tepary bean cell suspensions and whose initial pH was 4.5 increased gradually to about 5.0 within 12 days of culture. The pH of the culture media remained around 5.0 regardless of the initial pH values (4.5 and 5.3). However, the pH appeared to be relatively constant at 4.0 ± 0.1 for five days. This suggested that the cultures had to be transferred to a fresh medium every 4-5 days to maintain the pH of the media at 4.0 ± 0.1 and to maximise the toxic effects of aluminum.